Enhanced Spin Transfer Torque efficiency in Fe-HfO2/h-BN/Al2O3-Fe compared to existing Fe-MgO-Fe Magnetic Tunnel Junction Device - Thapa, Abinash; Bhutia, Pema Rinzing; Chettri, Bibek; Pradhan, Prashanta Chandra; Sharma, Bikash (Devices for Integrated Circuit, 2025)
Novel MTJs structure comprising of LDMs (MgO, Al 2 O 3 , h-BN and HfO 2 ) as tunnel layer sandwiched between Fe as ferromagnetic (FM) layer is designed for novel magnetic random access memory (MRAM) application. MTJLab Tool with inbuilt non-equilibrium Green's function (NEGF) model avails in calculating the spin transfer torque (STT) property of MTJs device. As STT define the critical parameters such as switching current density, thermal stability, torque asymmetry and reliability of MTJs. Amongst, HfO 2 and h-BN device showed the highest difference in STT components i.e., 1 mA and 0.8 mA along with higher number of stable and accessible memory states. Hence, they are considered as an ideal candidate for implementation as tunnel layer in advance MTJs device.